2016
DOI: 10.1609/aimag.v37i4.2687
|View full text |Cite
|
Sign up to set email alerts
|

Challenges in Building Highly Interactive Dialogue Systems

Abstract: Spoken dialog researchers have recently demonstrated highly-interactive systems in several domains. This paper considers how to build on these advances to make systems more robust, easier to develop, and more scientifically significant. We identify key challenges whose solution would lead to improvements in dialog systems and beyond.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
21
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
5
4
1

Relationship

1
9

Authors

Journals

citations
Cited by 28 publications
(24 citation statements)
references
References 71 publications
1
21
0
Order By: Relevance
“…For example, the popular GeMAPS set, designed for paralinguistic inference from prosody, treats energy and pitch features as separate streams, meaning that it is unable to capture alignment phenomena at all [43]. However, the current study has identified disalignment-related functions that include aspects that are very widely relevant -including for better second language teaching to foster communicative effectiveness, improving speech synthesis to more effectively convey dialog intentions, improving dialog act recognition, and better tracking of user intentions and attitudes in dialog systems [44]. Thus future work aiming to better understand peak alignment phenomenon is likely to have not only theoretical importance but also great practical value.…”
Section: Summary and Open Questionsmentioning
confidence: 92%
“…For example, the popular GeMAPS set, designed for paralinguistic inference from prosody, treats energy and pitch features as separate streams, meaning that it is unable to capture alignment phenomena at all [43]. However, the current study has identified disalignment-related functions that include aspects that are very widely relevant -including for better second language teaching to foster communicative effectiveness, improving speech synthesis to more effectively convey dialog intentions, improving dialog act recognition, and better tracking of user intentions and attitudes in dialog systems [44]. Thus future work aiming to better understand peak alignment phenomenon is likely to have not only theoretical importance but also great practical value.…”
Section: Summary and Open Questionsmentioning
confidence: 92%
“…They could be used for predicting a player's likely future actions from his or her prosody, or to help a robot player choose his actions based on a human player's utterance prosody. More generally, models of this kind could be useful for creating systems better able to coordinate their actions with human partners [42], for situated-action domains and beyond.…”
Section: Summary Directions For Future Work and Potential Valuementioning
confidence: 99%
“…Dialogue management for spoken dialogue systems is a challenging research domain due in part to difficulties arising from limited resources, the imperfection of technologies on which dialogue management is dependent, and of course the complexities of natural human conversation (Glass, 1999;Ward and DeVault, 2015). Within a conventional dialogue manager, an explicit dialogue state tracker is a key component that attempts to track both interlocutors' contributions to the exchange.…”
Section: Introductionmentioning
confidence: 99%